Return to play, performance, and value of National Basketball Association players following Achilles tendon rupture - Chauhan, A.; Stotts, J.; Ayeni, O. R.; Khan, M. (The Physician and Sportsmedicine, 2021)
Background: Achilles tendon ruptures are devastating injuries for National Basketball Association (NBA) players: prior studies have demonstrated decreased performance following return-to-play, but none have evaluated the effect of injury on rate-adjusted contextual statistics to assess the true change in performance. Additionally, there exists a paucity of data on the independent impact on defensive performance following return.